2020
DOI: 10.1002/ame2.12124
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of adult right ventricle failure in ovine using a graded, animal‐specific pulmonary artery constriction model

Abstract: BackgroundRight ventricle failure (RVF) is associated with serious cardiac and pulmonary diseases that contribute significantly to the morbidity and mortality of patients. Currently, the mechanisms of RVF are not fully understood and it is partly due to the lack of large animal models in adult RVF. In this study, we aim to establish a model of RVF in adult ovine and examine the structure and function relations in the RV.MethodsRV pressure overload was induced in adult male sheep by revised pulmonary artery con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…The stark differences in the elasticity between the free walls and septum can explain in vivo findings of the different contributions of the septum and free walls to the overall ventricular function. Assuming the similar mechanical properties and contractility of the septum and LV free wall, we would expect 16–35% of the cardiac work to be contributed by the septum (versus 65–84% contribution by the LV free wall), based on its volume fraction from the sheep and human data [ 31 , 32 ]. However, Ostenfeld et al reported that, in healthy subjects, the septum contraction contributed only ~8% of the stroke volume, while the LV free wall contributed ~96% of the stroke volume [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stark differences in the elasticity between the free walls and septum can explain in vivo findings of the different contributions of the septum and free walls to the overall ventricular function. Assuming the similar mechanical properties and contractility of the septum and LV free wall, we would expect 16–35% of the cardiac work to be contributed by the septum (versus 65–84% contribution by the LV free wall), based on its volume fraction from the sheep and human data [ 31 , 32 ]. However, Ostenfeld et al reported that, in healthy subjects, the septum contraction contributed only ~8% of the stroke volume, while the LV free wall contributed ~96% of the stroke volume [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were shown by Stephensen et al where ~7% of the septal motion contributed to the LV stroke volume [ 34 ]. Similarly, if we treat the septum as part of the RV chamber, it contributes somewhat similarly as the RV free wall in pumping, where 36–54% of cardiac work is attributed to the septum (versus 45–64% contribution by the RV free wall) [ 31 , 32 ]. Thus, the mechanical differences between the septum and ventricles found in our study suggests that the septal wall is not ‘similar’ to the ventricular free walls, and the mechanical difference may be linked to the altered muscle shortening velocity, leading to a ‘weaker’ contribution to the overall cardiac function than that of the ventricle free walls.…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model of PH (Sugen+hypoxia), the ratio of collagen type I/III was increased in the diseased RV and it was mainly attributed to the increase in type I collagen [78]. But in a recent ovine model of PH, type III collagen rather than type I collagen was found to be increased more significantly in the RV [51]. While both studies used Picrosirius Red stained histology samples to quantify collagen isoforms in the RV, these results need to be confirmed by other quantitative methods in future studies.…”
Section: Fibrotic Changes In Hypertensive LV and Rvmentioning
confidence: 93%
“…Because mature collagen is birefringent and the Picrosirius Red stain can enhance the birefringency of collagen, collagen fibers can be visualized better and in more details under polarized light. It also enables a quick examination of types I and III collagen in CV tissues due to the different fiber thickness [50,51]. Alternatively, the elastin is often examined by the Verhoeff-Van Gieson (VVG) stain [52] and the glycosaminoglycans (GAGs) and proteoglycans are examined by the Alcian blue stain [53].…”
Section: Biochemical and Biological Measurementsmentioning
confidence: 99%
“…The information derived from this approach can significantly improve the diagnosis and prognosis that are solely based on global functional metrices (e.g., end-diastolic pressure-volume relation). Second, the design of biomaterials for cardiac tissue engineering and regenerative medicine encompasses a wide range of substrate elasticity from sub- to supra- physiological stiffnesses (20 kPa–92 MPa), as we recently reviewed ( Nguyen-Truong et al, 2020a ). There are two layers of problems here.…”
Section: Introductionmentioning
confidence: 99%